Tingkat Pengetahuan Masyarakat Terhadap Penggunaan Obat Antibiotik Pada Anak Di Dusun X Kabupaten Klungkung - Deviana Gayatri, Ni Putu Ayu; Artika, Made Prita; Udi, Wahyuni W (Journal Pharmactive, 2024)
Inappropriate use of oral antibiotics is still found in the pediatric age group. Based on research by the Indonesian Antimicrobial Resistance Agency (AMRIN), it shows that 46% - 54% of antibiotic use in children was found to be inappropriate and not in accordance with the label. This study aims to determine the level of public knowledge regarding the use of antibiotics in children in Dusun X in Klungkung Regency in 2023. The method used in this study is quantitative descriptive with a cross-sectional approach. Sampling was carried out using a purposive sampling technique, namely distributing questionnaires in the form of a google form. This study involved 79 respondents, parents of patients aged 17-55 years. Based on the results of this study, it was found that the level of public knowledge regarding the use of antibiotics in children with a good level of knowledge of 7 respondents or (8.9%), a sufficient level of knowledge of 59 respondents or (74.7%), and a low level of knowledge of 13 respondents (16.5%). Keywords: Pediatric, knowledge, antibiotic, resistance